The effect of abdominal massage on bilirubin levels in term infants receiving phototherapy: A randomized controlled trial - Köse, Selmin; Gözen, Duygu; Karada? Aytemiz, Özge Eda; Ça?layan, Sabiha (My University, 2024)
Background: The incidence of neonatal hyperbilirubinemia in Europe and the United States is estimated to be 3.2 and 4.4 per 10,000 live births, respectively. Abdominal massage for hyperbilirubinemia is considered a safe complementary treatment for infants that may increase number of defecations and decrease bilirubin levels. Purpose: This study was designed as a randomized controlled trial to determine the effect of abdominal massage on bilirubin levels in term infants receiving phototherapy. Methods: The sample consisted of 43 term newborns (intervention group: 23; control group: 20) who received phototherapy in a university hospital between June 2019 and February 2021. Information and observation forms were used for data collection. The intervention group received 6 abdominal massages over 2 days, performed 3 times a day, 6 hours apart, and lasting 5 minutes each. Results: Transcutaneous bilirubin levels and heart rate were significantly lower in the intervention group than in the control group at 48 hours (P =.015 and P =.033, respectively). Number of defecations was higher in the intervention group at 24 hours (P =.007) but there was no significant difference at 48 hours. The decrease in serum bilirubin between 24 and 48 hours was significantly greater in the intervention group (P =.005). Implication for Practice and Research: Abdominal massage was effective in reducing bilirubin levels and may increase the number of defecations. Providing massage training to the parents of infants who are discharged early could be a protective approach to prevent the rise in bilirubin levels.
Keywords: Abdominal Massage; Hyperbilirubinemia; Nursing; Phototherapy; Term Infants